Increasing incidence of Gram-negative organisms in bacterial agents isolated from diabetic foot ulcers - Turhan, Vedat; Mutluoglu, Mesut; Acar, Ali; Hatipoglu, Mustafa; Onem, Yalcın; Uzun, Gunalp; Ay, Hakan; Oncul, Oral; Gorenek, Levent (The Journal of Infection in Developing Countries, 2013)
Introduction: In the present study, we sought to identify the bacterial organisms associated with diabetic foot infections (DFIs) and their antibiotic sensitivity profiles. Methodology: We retrospectively reviewed the records of wound cultures collected from diabetic patients with foot infections between May 2005 and July 2010. Results: We identified a total of 298 culture specimens (165 [55%] wound swab, 108 [36%] tissue samples, and 25 [9%] bone samples) from 107 patients (74 [69%] males and 33 [31%] females, mean age 62 ± 13 yr) with a DFI. Among all cultures 83.5% (223/267) were monomicrobial and 16.4% (44/267) were polymicrobial. Gram-negative bacterial isolates (n = 191; 61.3%) significantly outnumbered Gram-positive isolates (n = 121; 38.7%). The most frequently isolated bacteria were Pseudomonas species (29.8%), Staphylococcus aureus (16.7%), Enterococcus species (11.5%), Escherichia coli (7.1%), and Enterobacter species (7.1%), respectively. While 13.2% of the Gram-negative isolates were inducible beta-lactamase positive, 44.2% of Staphylococcus aureus isolates were methicillin resistant. Conclusions: Our results support the recent view that Gram-negative organisms, depending on the geographical location, may predominate in DFIs.